Laboratory prediction of the requirement for renal replacement in acute falciparum malaria. - Hanson, J; Hasan, M; Royakkers, A; Alam, S; Charunwatthana, P; Maude, R; Douthwaite, S; Yunus, E; Mantha, M; Schultz, M; Faiz, M; White, N; et al. (BioMed Central, 2011)
BACKGROUND: Acute renal failure is a common complication of severe malaria in adults, and without renal replacement therapy (RRT), it carries a poor prognosis. Even when RRT is available, delaying its initiation may increase mortality. Earlier identification of patients who will need RRT may improve outcomes. METHOD: Prospectively collected data from two intervention studies in adults with severe malaria were analysed focusing on laboratory features on presentation and their association with a later requirement for RRT. In particular, laboratory indices of acute tubular necrosis (ATN) and acute kidney injury (AKI) that are used in other settings were examined. RESULTS: Data from 163 patients were available for analysis. Whether or not the patients should have received RRT (a retrospective assessment determined by three independent reviewers) was used as the reference. Forty-three (26.4%) patients met criteria for dialysis, but only 19 (44.2%) were able to receive this intervention due to the limited availability of RRT. Patients with impaired renal function on admission (creatinine clearance < 60 ml/min) (n = 84) had their laboratory indices of ATN/AKI analysed. The plasma creatinine level had the greatest area under the ROC curve (AUC): 0.83 (95% confidence interval 0.74-0.92), significantly better than the AUCs for, urinary sodium level, the urea to creatinine ratio (UCR), the fractional excretion of urea (FeUN) and the urinary neutrophil gelatinase-associated lipocalcin (NGAL) level. The AUC for plasma creatinine was also greater than the AUC for blood urea nitrogen level, the fractional excretion of sodium (FeNa), the renal failure index (RFI), the urinary osmolality, the urine to plasma creatinine ratio (UPCR) and the creatinine clearance, although the difference for these variables did not reach statistical significance. CONCLUSIONS: In adult patients with severe malaria and impaired renal function on admission, none of the evaluated laboratory indices was superior to the plasma creatinine level when used to predict a later requirement for renal replacement therapy.